A cross-border outbreak of Salmonella Bareilly cases confirmed by whole genome sequencing, Czech Republic and Slovakia, 2017 to 2018 - Labská, Klára; Špačková, Michaela; Daniel, Ondřej; Včelák, Josef; Vlasáková, Veronika; Černý, Tomáš; Gelbíčová, Tereza; Florianová, Martina; Karpíšková, Renáta; Gavačová, Dagmar; Štefkovičová, Mária; Orlíková, Hana (Euro surveillance, 2021)
In August 2017, an increased incidence of Salmonella Bareilly was detected in the Czech Republic. An investigation was conducted with Slovakia to confirm the outbreak and identify the source. Probable outbreak cases were defined as cases with laboratory-confirmed S. Bareilly reported in either of the national surveillance systems, and/or the Czech and Slovak National Reference Laboratory databases from July 2017. Confirmed cases had the pulsed-field gel electrophoresis (PFGE) outbreak pulsotype or up to 5 alleles difference from outbreak cluster members by core genome multilocus sequence typing (cgMLST). PFGE and whole genome sequencing were used for isolate comparison. The same trawling questionnaire was used in both countries. By the end of October 2018, 325 cases were identified. Among 88 human S. Bareilly isolates analysed by PFGE, 82 (93%) shared an identical pulsotype; cgMLST of 17 S. Bareilly human isolates showed 1-2 allele difference. The trawling questionnaire excluded consumption of unusual or imported foods. In September 2018, an isolate closely related to the outbreak isolates was identified in a powdered egg product. A spray dryer was recognised as the contamination source and the production plant was closed. Using molecular typing methods, we detected a diffuse cross-border outbreak caused by S. Bareilly.
Keywords: Electrophoresis, Gel, Pulsed-Field; sekvenování celého genomu; Genome, Bacterial; Whole Genome Sequencing; food- and water-borne diseases; multilokusová sekvenční typizace; Disease Outbreaks; Czech Republic; powdered egg product; Salmonella; outbreak; lidé; WGS; Česká republika; Slovakia; Humans; pulzní gelová elektroforéza; Multilocus Sequence Typing; spray dryer; epidemický výskyt choroby; genom bakteriální; Salmonella Bareilly; Slovenská republika